The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1542/peds.2004-1605
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Fungemia in Hospitalized Pediatric Inpatients Over 11 Years at a Tertiary Care Institution

Abstract: Episodes of fungemia increased significantly over 11 years as compared with a moderate increase in positive fungal cultures and were associated with high all-cause mortality rates. More sensitive assays for early identification of fungal bloodstream infections are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 21 publications
8
57
1
5
Order By: Relevance
“…Using a intraperitoneal murine infection model, it has been demonstrated that Cp ΔΔlip1-ΔΔlip2 cells were able to accumulate less in the kidney, liver and spleen of BALB/c mices 2 days post infection [34], but these mutant cells were eradicated within 4 days after the infection, which was significantly faster than clearance of wild type yeast [34]. As C. parapsilosis is one of the leading species associated with neonatal invasive infections, efforts have been applied to developing a suitable model to mimic newborn-related candidiasis [67][68][69]. Using newborn Sprague-Dawley rats, Trofa et al demonstrated that premature neonates were highly susceptible to candidal infections.…”
Section: In Vivo Infection Models To Study C Parapsilosis Lipase Funmentioning
confidence: 99%
“…Using a intraperitoneal murine infection model, it has been demonstrated that Cp ΔΔlip1-ΔΔlip2 cells were able to accumulate less in the kidney, liver and spleen of BALB/c mices 2 days post infection [34], but these mutant cells were eradicated within 4 days after the infection, which was significantly faster than clearance of wild type yeast [34]. As C. parapsilosis is one of the leading species associated with neonatal invasive infections, efforts have been applied to developing a suitable model to mimic newborn-related candidiasis [67][68][69]. Using newborn Sprague-Dawley rats, Trofa et al demonstrated that premature neonates were highly susceptible to candidal infections.…”
Section: In Vivo Infection Models To Study C Parapsilosis Lipase Funmentioning
confidence: 99%
“…Although the yeast form can bind to gut mucosal membranes with further colonization (20,49), it is thought that the filamentous morphology provides some advantage during interaction with the mammalian immune system as a part of fungal anti-host defense, and the ability of C. albicans to rapidly and reversibly switch between yeast and filamentous morphologies is crucial to its pathogenicity (16,55,65,82). In recent years, Candida infections ranked as the fourth most common cause of bloodstream infections and are the leading cause of life-threatening nosocomial fungal infections (1,87). The risk of developing opportunistic bloodstream infections is greatly increased in patients who are severely immunocompromised.…”
mentioning
confidence: 99%
“…Fungal isolates are obtained in as many as 5% of all bacteremia and fungemia cases, and most of fungal isolates are Candida spp. (1,8). Furthermore, episodes of fungemia have increased significantly over the years (1).…”
Section: Discussionmentioning
confidence: 99%
“…(1,8). Furthermore, episodes of fungemia have increased significantly over the years (1). Universal amplification of fungal isolates is different from that of bacteria, so one more PCR amplification is necessary to detect fungi isolated by the chip.…”
Section: Discussionmentioning
confidence: 99%